CREANDO: Tool for creating pervasive games to increase the learning motivation in higher education students - Arango-López, Jeferson (2019)
The pervasive games (PG) have had a great reception in recent years. This kind of games combines the virtual world with the real world to generate extensions of reality in terms of time, space and social interaction. These extensions have involved users in experiences as varied as those exposed by augmented reality and the location of the player or mixed reality scenarios. In the educational context, games have been integrated little by little into learning processes. Specifically, PG have shown to have a higher level of immersion in people's daily activities. Therefore, a greater impact is generated when integrating the technologies of the PG and the narrative of a story that is told through the gaming experience. In order to explore some fields, we focus the study on the narrative and geolocation applied to close spaces, it is a way of giving an enriched experience to the player through a digital transformation perspective. For this reason, it is necessary to have a platform that allows the creation and edition of PG based on narrative to increase the motivation of higher education students. This article describes the creation of a platform that integrates tools for creating stories and editing narrative content in the game experiences. The main objective is focused on increasing the motivation of students in educational processes. Specifically, the platform allows the creation of pervasive gaming experiences in closed spaces on university campuses. In addition, the results of a test case developed with the platform and its validation through statistical tools and gameplay metrics are exposed, thus demonstrating the increase in students' motivation through the use of PG.